Lidia's a pot, a pan, and a bowl : simple recipes for perfect meals - Bastianich, Lidia; Manuali, Tanya Bastianich (Alfred A. Knopf, 2021)
"More than 100 recipes that use just one (or two) pots, pans, or bowls; from Lidia Bastianich"--